2015
DOI: 10.1111/1744-7917.12212
|View full text |Cite
|
Sign up to set email alerts
|

Morphology versus DNA barcoding: two sides of the same coin. A case study of Ceutorhynchus erysimi and C. contractus identification

Abstract: Genotyping of 2 well-known weevil species from the genus Ceutorhynchus (Coleoptera: Curculionidae) distributed in west Palearctic, C. erysimi and C. contractus, revealed phenotype versus genotype inconsistencies in a set of 56 specimens (25 C. erysimi and 31 C. contractus) collected from 25 locations in Serbia and Montenegro. An analysis of the mitochondrial cytochrome oxidase subunit I gene (COI), widely used as a barcoding region, and a nuclear gene, elongation factor-1α (EF-1α), revealed stable genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The results presented here, confirm the proposal (Fumanal et al, 2005;Fumanal et al, 2004b) that Ceutorhynchus species (Laffin et al, 2005a) as confirmed by the divergence observed with the congeneric species used as outgroups. However, the level of divergence detected here is in the same order of magnitude as the one observed between two sister species, C. erysimi and C. contractus (Stepanović et al, 2015). Likewise, although the ABGD procedure tends to consider the three different lineages as a single species, the PTP analysis suggests that the Lepidium host race may potentially represent cryptic species or subspecies.…”
Section: Evolutionary History Of C Assimilissupporting
confidence: 54%
See 1 more Smart Citation
“…The results presented here, confirm the proposal (Fumanal et al, 2005;Fumanal et al, 2004b) that Ceutorhynchus species (Laffin et al, 2005a) as confirmed by the divergence observed with the congeneric species used as outgroups. However, the level of divergence detected here is in the same order of magnitude as the one observed between two sister species, C. erysimi and C. contractus (Stepanović et al, 2015). Likewise, although the ABGD procedure tends to consider the three different lineages as a single species, the PTP analysis suggests that the Lepidium host race may potentially represent cryptic species or subspecies.…”
Section: Evolutionary History Of C Assimilissupporting
confidence: 54%
“…Despite numerous taxonomic revisions of the genus (Colonnelli, 1993;Colonnelli, 2004;Hoffman, 1954;Tempère and Péricart, 1989), taxonomical and nomenclatural issues represent the main constraints in studying this important weevil group, as highlighted by Stepanović et al (2015). In this context, although it was not the main aim of this study, we confirmed the distinction between the cabbage seedpod weevil, C. obstrictus (Marsham) [= C. assimilis (Paykull)], a serious European pest of canola or oil seed rape, which is invasive in North America (Dosdall and Mason, 2010;Laffin et al, 2005b), and C. assimilis [= C. pleurostigma].…”
Section: Evolutionary History Of C Assimilismentioning
confidence: 99%
“…Moreover, molecular identification might be effectively applied to classify the immature stages of triatomines, as traditional taxonomic methods are difficult to use when distinguishing nymphs, especially considering the species complexes that exhibit large morphological and chromatic variation [28]. However, molecular identification will not take the place of morphological systematics because it relies on species definitions produced from morphological analyses [49]; hence, both approaches should be applied to provide effective, efficient and accurate species identifications [50, 51], and the integration of morphological and molecular methods is indicated for species recognition of T. rubrofasciata in future entomological surveys in China [6].…”
Section: Discussionmentioning
confidence: 99%
“…All populations sharing the Jura genital structure are found in haplotype clusters separated from cluster B by three mutational steps. Asymmetric introgression is regarded the most probable cause of this kind of discrepancies (Stephanović et al 2016). Given the considerable geographic distance, a recent involvement LG -Lake Geneva, LCo -Lake Constance, LM -Lake Maggiore, LC -Lake Como.…”
Section: Integration Of Datasetsmentioning
confidence: 99%